Ethnic‐racial socialization among Black, Latinx, and White parents of elementary school‐age children. (25th December 2021) - Williams, Amber D.; Banerjee, Meeta
Abstract: This study sought to (1) understand the differences in ethnicity/race‐related values, concerns, and ethnic‐racial socialization (ERS) among 156 Black, Latinx, and White parents of elementary‐school aged children and (2) examine how parents' various ethnicity/race‐related values and concerns related to their ERS practices. We found that Black and Latinx parents were more likely than White parents to send messages about celebrating people of color, while Latinx parents were more likely to send egalitarian messages than White parents. We also found that parents who expressed a fear of discussing race were less likely to send all ERS messages, except messages promoting out‐group mistrust. Additionally, parents who valued diversity over competing benefits were more likely to send all ERS messages, except egalitarian messages. Other results suggest relations between parents' ethnicity/race‐related concerns and values and their ERS practices. The implications of this work for social issues related to ethnic‐racial socialization strategies are discussed.